Frequency-Limited Model Reduction for Linear Positive Systems: A Successive Optimization Method - Yingying Ren; Qian Wang (Applied Sciences, 2023)
This paper studies frequency-limited model reduction for linear positive systems. Specifically, the objective is to develop a reduced-order model for a high-order positive system that preserves the positivity, while minimizing the approximation error within a given <semantics>H∞</semantics> upper bound over a limited frequency interval. To characterize the finite-frequency <semantics>H∞</semantics> specification and stability, we first present the analysis conditions in the form of bilinear matrix inequalities. By leveraging these conditions, we derive convex surrogate constraints by means of an inner-approximation strategy. Based on this, we construct a novel iterative algorithm for calculating and optimizing the reduced-order model. Finally, the effectiveness of the proposed model reduction method is illustrated with a numerical example.